Evaluation of biocatalysts synthesized with lipase from Pseudomonas cepacia supported on glycol-modified MOF-199 in the synthesis of green biodiesel - Martínez Gil, José Manuel; Vivas-Reyes, Ricardo; Bastidas-Barranco, Marlón José; Giraldo, Liliana; Moreno-Piraján, Juan Carlos (Frontiers in Sustainability, 2022)
In this research, we report on the synthesis and characterization of biocatalysts extracts. It was used MOF-199 and Pseudomonas cepacia lipase as support which is an agent for the breakdown of saturated, monounsaturated, and polyunsaturated fatty acids: the main components of oil palm (Elaeis guineensis), used for obtaining green biodiesel. Pseudomonas cepacia lipase (PCL) was used as an enzyme supported by adsorption on MOF-199 (MOF-199-PCL). Another part of MOF-199 was modified with glycol as a carbon source, to which PCL is supported to obtain the MOF (Gly@MOF-199-PCL) modified. MOF-199 was modified by calcining a sample of this MOF at 900°C for two hours at a heating rate of 7°C/min in an inert atmosphere and then stored in a desiccator to protect it from moisture before proceeding to adsorb PCL. In both biocatalysts (MOF-199-PCL and Gly@MOF-199-PCL), both after the transesterification reaction and the supernatant liquid were characterized by infrared spectroscopy, Raman spectroscopy, SEM-EDS, and gas chromatography coupled to mass. The results show that the outcomes obtained from the instrumental part show that both biocatalysts produce green biodiesel, which is a novel contribution to these systems.